2021
DOI: 10.1016/j.celrep.2021.108814
|View full text |Cite|
|
Sign up to set email alerts
|

TRPS1 drives heterochromatic origin refiring and cancer genome evolution

Abstract: Highlights d TRPS1 interacts with replication machinery and binds to H3K9me3-marked origins d TRPS1 encourages chromatin loading of APC/C leading to uncontrolled origin refiring d TRPS mutations abolish TRPS1-promoted replication boosting and breast carcinogenesis d TRPS1 overexpression drives cancer genome evolution and therapeutic resistance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…TRPS1 is reported to be a transcriptional repressor that binds specifically to GATA sequences and represses the expression of GATA-regulated genes which function in vertebrate development, especially in the process of chondrocyte proliferation and differentiation [ 41 , 42 ]. Some studies have suggested that TRPS1 may also act as a critical modulator in mammary epithelial cell growth, differentiation, and breast cancer development via epithelial–mesenchymal transformation, DNA replication, and mitosis [ 43 , 44 ]. A recent study by Ai et al reported that TRPS1 could serve as a sensitive and specific marker for breast carcinomas [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPS1 is reported to be a transcriptional repressor that binds specifically to GATA sequences and represses the expression of GATA-regulated genes which function in vertebrate development, especially in the process of chondrocyte proliferation and differentiation [ 41 , 42 ]. Some studies have suggested that TRPS1 may also act as a critical modulator in mammary epithelial cell growth, differentiation, and breast cancer development via epithelial–mesenchymal transformation, DNA replication, and mitosis [ 43 , 44 ]. A recent study by Ai et al reported that TRPS1 could serve as a sensitive and specific marker for breast carcinomas [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPS1 is a transcription factor classically linked to skeletal development, as subjects with germline alterations in the Trps1 gene suffer from autosomal dominant trichorhinophalangeal syndromes with characteristic craniofacial abnormalities (Lüdecke et al, 2001; Momeni et al, 2000). More recently, TRPS1 has been implicated in tumorigenesis in breast cancer (Ai et al, 2021; Cornelissen et al, 2020) and osteosarcoma (Li et al, 2015) potentially through promotion of dysregulated cell replication resulting in accumulation of genomic aberrations (Yang et al, 2021). Functionally, TRPS1 is thought to function uniquely as a transcriptional repressor via its GATA domain (Malik et al, 2002), although notably TRPS1 contains two Ikaros-like domains whose specific functions are poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies also reported a high sensitivity and specificity of TRPS1 for primary extramammary Paget disease, 44 and differential staining of TRPS1 in various types of malignant and benign cutaneous sweat glands. 45 Several studies have proposed oncogenic 46,47 or tumor suppressive 5,6 roles for TRPS1. The availability of clinic-pathologic data for several tumor cohorts enabled us to interrogate the potential clinical significance of aberrant TRPS1 expression in vivo.…”
Section: Discussionmentioning
confidence: 99%